Post-traumatic stress disorder and its relationship to school violence In elementary school students (Journal of the College of Basic Education, 2022)
The research aims to identify the nature of the relationship between post-traumatic stress disorders and violent behavior among primary school students. The researcher built two tools: the post-traumatic stress disorder scale, which consists of two parts: {the first part is diagnostic and consists of (14) items, and the second part is used for measurement and consists of (32) items}.